2019
DOI: 10.1038/s41598-019-47138-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the binding of diverse ligands within the Ah receptor ligand binding domain

Abstract: The Ah receptor (AhR) is a ligand-dependent transcription factor belonging to the basic helix-loop-helix Per-Arnt-Sim (bHLH-PAS) superfamily. Binding to and activation of the AhR by a variety of chemicals results in the induction of expression of diverse genes and production of a broad spectrum of biological and toxic effects. The AhR also plays important roles in several physiological responses, which has led it to become a novel target for the development of therapeutic drugs. Differences in the interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 70 publications
6
51
0
1
Order By: Relevance
“…The sequence alignment of top 10 templates used by I-TASSER to homology model of the hAhR LBD is illustrated in Figure 4C. In accordance with previous modelling approaches [13,27], I-TASSER also identified PAS structures as the best template for hAhR modelling, with about 50% of sequence similarity. Out of the five models generated by I-TASSER, the model with the highest C-Score (−0.05) was selected for further study.…”
Section: Molecular Docking Studiessupporting
confidence: 74%
See 1 more Smart Citation
“…The sequence alignment of top 10 templates used by I-TASSER to homology model of the hAhR LBD is illustrated in Figure 4C. In accordance with previous modelling approaches [13,27], I-TASSER also identified PAS structures as the best template for hAhR modelling, with about 50% of sequence similarity. Out of the five models generated by I-TASSER, the model with the highest C-Score (−0.05) was selected for further study.…”
Section: Molecular Docking Studiessupporting
confidence: 74%
“…Ligand-dependent activation of the AhR can result in an extremely diverse spectrum of biological and toxic effects that occur in a ligand-, species-and tissue-specific manner [26]. On the basis of a novel computational approach for molecular docking to the homology model of the AhR LBD, specific residues within the AhR binding cavity that play a critical role in binding of three distinct groups of chemicals were recently predicted and experimentally confirmed by Giani Tagliabue et al [27]. A ligand-selective structural hierarchy controlling dimerization of the AhR with ARNT and the recognition of target DNA was described by Seok et al [28].…”
Section: Discussionmentioning
confidence: 98%
“…Here, through the study of the candidate driver mutation AHR Q383H, we provided a validation of the accuracy of our prediction. The importance of Q383 site in AhR activity (Q377 as the mouse equivalent) was previously suggested by its structural impact on AhR ligand binding affinity and preference by shape and H-bond [ 76 78 ]. We showed that the AHR Q383H mutation and other genetic alterations affecting the AhR pathway ( AHR and ARNT amplifications) were associated with dependency to AHR expression or activity and were enriched in the luminal subtype of BCa.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, citrate binding to the PAS domain of sensor histidine kinase CitA was shown to induce a flexion of the central β-sheet around the ligand that then propagates to the transmembrane domain of the protein [29]. Although the three-dimensional structure of the AhR PASB domain has been obtained by homology modeling [30], and both ligand binding [31] and dimerization with ARNT [32,33] have been computationally simulated, to date, the molecular effects of ligand binding on the mechanism of AhR transformation are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%